A content analysis on state human trafficking statutes: how does the legal system acknowledge survivors in the United States (US)? - Branscum, Caralin (Crime, law and social change, 2021)
Human trafficking is an egregious violation of basic human rights that has reached global proportions. Despite the gradual proliferation of social science research and policy endeavors, a contemporary understanding of state human trafficking statutes has received limited discussion. Existing commentary tends to underserve survivor experiences in the law. Using a database of 982 human trafficking state statutes, this study seeks to describe the landscape of how the law acknowledges survivors. In doing so, we found that states acknowledge survivors through 1. formal agency guidelines, 2. survivor rights and services, and 3. education and awareness for the general public. Findings suggest that the nation’s human trafficking statutes are best characterized as a patchwork of laws. We conclude by making recommendations for future legislative reform.